Cartilage Surgery in Overweight Patients: Clinical and MRI Results after the Autologous Matrix-Induced Chondrogenesis Procedure. (8th May 2018) - Lahner, Matthias; Ull, Christopher; Hagen, Marco; von Schulze Pellengahr, Christoph; Daniilidis, Kiriakos; von Engelhardt, Lars Victor; Lahner, Nina; Teske, Wolfram
Abstract : Modern orthopaedic surgery provides a variety of techniques for cartilage repair. The Autologous Matrix-Induced Chondrogenesis (AMIC) procedure is a single-step technique with a collagen I/III scaffold for the treatment of full-thickness cartilage lesions. The aim of the study was to analyze the outcome of the AMIC procedure in overweight patients with knee cartilage defects. Overweight patients treated with AMIC surgery were followed up by clinical and MRI examination. 9 patients with a cartilage defect of the knee with a mean lesion size of2 . 1 ± 1 . 2 cm 2 and an average body mass index (BMI) of 29.3 were available for the follow-up. The Lysholm Score was significantly improved by the AMIC procedure (38 to 67, p ≤ 0.008 ). The VAS Score was significantly lower after the procedure (9 to 3, p ≤ 0.018 ). In the postoperative MOCART Scale, the scaffold reached defect covering of 80%. However, 2 patients had to be revised due to persisting knee pain. The AMIC procedure enhances pain reduction and gain of knee function for cartilage defects of overweight patients. However, in cases of an increased BMI, the patient had to be informed that success rate is reduced despite good defect covering.